2023
DOI: 10.4269/ajtmh.22-0489
|View full text |Cite
|
Sign up to set email alerts
|

Drug Use Practices and Self-Treatment for Suspected Malaria in Ibadan, Nigeria

Abstract: Antimalarial drug failures have been reported anecdotally in Nigeria, and malarial self-treatment practices could be a contributing factor. This study was designed to assess the pattern of drug use practices and self-treatment options among caregivers in Ibadan, Nigeria. We carried out a descriptive cross-sectional study among 283 study participant pairs (children under 5 years of age with suspected malaria and their caregivers). Structured questionnaires were used as research instruments. The results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Regular monitoring of anti-malaria drug efficacy is needed to inform treatment policies in malaria-endemic countries, and to ensure early detection of, and response to, drug resistance (WHO, 2023). Anti-malaria drug failures have been reported anecdotally in Nigeria, and malaria self-treatment practices could be a contributing factor (Oluwayemi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular monitoring of anti-malaria drug efficacy is needed to inform treatment policies in malaria-endemic countries, and to ensure early detection of, and response to, drug resistance (WHO, 2023). Anti-malaria drug failures have been reported anecdotally in Nigeria, and malaria self-treatment practices could be a contributing factor (Oluwayemi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In a research conducted in Ibadan, Nigeria, 69% of caregivers self-prescribed and self-managed malaria for children under 5 years old without immediate hospital visits, and 76.4% of the caregivers believed the most recommended and available anti-malaria drugs were ineffective (Oluwayemi et al, 2023). Oluwayemi et al (2023) also found out that, 44.2% of respondents preferred and used antibiotics as a treatment strategy for malaria, 13.2% used agbo (a locally made liquid extract of plants and roots), 12.5% used prayers, 19.6% used anti-malaria drugs and 57.1% of respondents stated that they always complete the standard anti-malaria dosage regimen (Oluwayemi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%